2013
DOI: 10.1186/2050-3385-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive integrated transponder tags on survival and growth of juvenile Atlantic salmon Salmo salar

Abstract: Background: A laboratory experiment was conducted to assess the potential impacts of surgically implanted 23 and 32 mm passive integrated transponder (PIT) tags on survival, growth, and body condition of juvenile Atlantic salmon Salmo salar. Rate of tag retention and healing of the tagging incision were also evaluated. Atlantic salmon of three different size classes (I: 80 to 99 mm fork length (FL), II: 100 to 119 mm FL, III: 120 to 135 mm FL) were allocated to each of five experimental treatment groups: contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 36 publications
(74 reference statements)
5
66
1
Order By: Relevance
“…Fish were then tagged with a 23 mm PIT tag (RI-TRP-RRHP, 134 kHz, 0.6 g mass in air; Texas Instruments, Plano, TX, USA) inserted into their body cavity. Larsen et al (2013) demonstrated that the retention of these tags in Atlantic salmon (Salmo salar) was 97% with no effects on mortality rate and growth. A condition factor (K) was calculated using Eqn 1.…”
Section: Materials and Methods Study Locationmentioning
confidence: 99%
“…Fish were then tagged with a 23 mm PIT tag (RI-TRP-RRHP, 134 kHz, 0.6 g mass in air; Texas Instruments, Plano, TX, USA) inserted into their body cavity. Larsen et al (2013) demonstrated that the retention of these tags in Atlantic salmon (Salmo salar) was 97% with no effects on mortality rate and growth. A condition factor (K) was calculated using Eqn 1.…”
Section: Materials and Methods Study Locationmentioning
confidence: 99%
“…The PIT tags weighed 0.036 g (between 0.2% and 0.5% of the dummy tag mass). In small salmonids, the impact of PIT tags has been negligible [32][33][34] therefore their weight was not included in tag burden calculations. Dummy and PIT tags were inserted in the experimental groups and the incisions of all fish were closed with two interrupted figure-eight sutures of absorbable 4-0 chromic gut.…”
Section: Experimental Treatmentmentioning
confidence: 99%
“…; Larsen et al . ). However, in the treatments with external tags and dummy transmitter, many of tag insertion areas were inflamed.…”
Section: Discussionmentioning
confidence: 97%
“…; Larsen et al . ), and PIT tagging has been used as a control treatment also in the earlier tagging studies (Hockersmith et al . ; Lacroix et al .…”
Section: Methodsmentioning
confidence: 99%